The Translation of Specialized Discriminative Expressions in Political Speeches within a CDA Framework - Ghafore, Mahmood Shafeeq; Hamad, Suha Rasheed (Integrated Journal for Research in Arts and Humanities, 2023)
Language is said to be the primary means of communication among humans and plays a significant role in daily living, including idea sharing and educating others about cultural differences. There are many different languages spoken around the world, and occasionally more than one in a single nation. Without a doubt, translation plays a minor role in language because it permits the sharing of ideas, cultures, and even points of view. Language is extremely crucial for communication and the exchange of knowledge and information among individuals who speak various languages. This study focuses on the manner in which discriminatory expressions and the role of CDA in discriminative expression are translated, as well as how translators handle these expressions when they appear in speeches by prominent Americans, such as John F. Kennedy and Martin Luther King, discussing racism between Black and White Americans.